A Tri-fusion Reporter Mouse Reveals Tissue-Specific FGF1B Promoter Activity in vivo - Liu, Shan-Wen; Hsu, Ching-Han; Chen, Mei-Ru; Chiu, Ing-Ming; Lin, Kurt M. (Scientific reports, 2019)
Transgenic mice harboring imaging reporters take full advantage of imaging technologies in studies using living mice. Here, we established a tri-fusion multimodal reporter gene containing fragments from firefly luciferase, enhanced green fluorescent protein, and herpes simplex virus type 1 thymidine kinase and generated tri-fusion reporter Tg mice. Fibroblast growth factor type 1 (FGF1), a multifunctional mitogen to a wide range of tissues, regulates proliferation of neural stem cells of the brain, where FGF1 expression is initiated through activation of the FGF1B (F1B) promoter. The reporter mouse under the control of the human F1B promoter enables visualization in vivo where F1B activity is elevated, including tissues not only in the brain but also in the nasopharynx, skull, spine, and testes, particularly in Leydig cells. Treating Tg mice with the alkylating agent busulfan, which is known to eradicate Leydig cells and disrupt spermatogenesis in mice, eliminated the reporter signals. Restoring Leydig cells recovered reporter expression, indicating that the reporter can be used as a surrogate marker for Leydig cells. The F1B tri-fusion reporter mouse model can be utilized in longitudinal monitoring of the health status of the male reproductive system, such as in studies exploring the toxicity of chemicals to spermatogenesis.